2015
DOI: 10.1179/1743285515y.0000000012
|View full text |Cite
|
Sign up to set email alerts
|

Freeze lining formation on water cooled refractory wall

Abstract: The experimental study was focused into effects of a ceramic refractory lining, covering a metallic cooling element, as well as to properties and microstructures of the freeze lining formed in such cases in copper smelting and converting slags. The modified heat transfer pattern, due to the ceramic refractory lining and its air gap(s), increases effectively the average freeze lining temperature, heating its cold face from 30 to 50°C of the direct contact close to 800–900°C, even with refractory thicknesses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As a first approximation, a number of simplifying assumptions can be made. For example, if under thermal steady state conditions the parameters are constant, and no refractory lining as in (Kalliala et al 2015) is present, the steady state thickness of the freeze lining (Δx FL,ss ) can be described by Equation (3) (Thonstad and Rolseth 1983;Verscheure et al 2006;Jansson et al 2014).…”
Section: Freeze Liningsmentioning
confidence: 99%
“…As a first approximation, a number of simplifying assumptions can be made. For example, if under thermal steady state conditions the parameters are constant, and no refractory lining as in (Kalliala et al 2015) is present, the steady state thickness of the freeze lining (Δx FL,ss ) can be described by Equation (3) (Thonstad and Rolseth 1983;Verscheure et al 2006;Jansson et al 2014).…”
Section: Freeze Liningsmentioning
confidence: 99%
“…The development of refractory lining technologies has been important in the flash smelting as the fluid iron silicate slags and occasionally and locally high copper concentrations are very aggressive to the vessel construction. Today, the operational conditions also allow the use of freeze linings, generated by effective heat flux through the refractory lining and assisted by cooling elements (Kalliala et al 2015). Those measures have extended the campaign lives of flash smelting vessels from the early few months duration to several years.…”
Section: Environmental Issues In Sulphide Smelting – the Finnish Solu...mentioning
confidence: 99%
“…Fallah-Mehrjardi, Hayes, and Jak (2014) studied the effect of bath chemistry on the freeze lining microstructure of a copper smelting slag at the laboratory scale using the cold probe technique and found that the freeze lining formed depended on the viscosity of the slag bath. Kalliala et al (2015) also used the cold probe technique in a refractory sleeve to show that the freeze lining composition depends on the cooling rate of the freeze lining during formation.…”
Section: Introductionmentioning
confidence: 99%
“…Little work has been done to model the thermomechanical aspects of freeze linings, despite several comments on aspects that mechanically challenge the freeze line integrity (Kalliala et al, 2015;Crivits, 2016;Zietsman, 2004). A thermomechanical model was produced by Campbell, Pericleous, and Gross (2002) that made use of a computational fluid mechanics (CFD) model coupled with a thermomechanical module to model the penetration, corrosion, and erosion of the refractory in a HIsmelt process.…”
Section: Introductionmentioning
confidence: 99%